2016
DOI: 10.1158/0008-5472.can-15-1629
|View full text |Cite
|
Sign up to set email alerts
|

Discordant Haplotype Sequencing Identifies Functional Variants at the 2q33 Breast Cancer Risk Locus

Abstract: The findings from genome-wide association studies hold enormous potential for novel insight into disease mechanisms. A major challenge in the field is to map these low risk association signals to their underlying functional sequence variants (FSVs). Simple sequence study designs are insufficient, as the vast numbers of statistically comparable variants and a limited knowledge of non-coding regulatory elements complicate prioritization. Furthermore, large sample sizes are typically required for adequate power t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The remaining 34 associated genes are located at known breast cancer susceptibility loci (Tables 2–3). Among them, 23 have not yet been implicated as genes responsible for association signals identified at these loci through expression quantitative trait loci (eQTL) and/or functional studies, and do not harbor GWAS or fine-mapping identified risk variants (Table 2), while the other eleven ( KLHDC7A 7 , ALS2CR12 31 , CASP8 31,32 , ATG10 9 , SNX32 33 , STXBP4 34,35 , ZNF404 8 , ATP6AP1L 9 , RMND1 17, L3MBTL3 6 , and RCCD1 10 ) had been reported as potential causal genes at breast cancer susceptibility loci or harbor GWAS or fine-mapping identified risk variants (Table 3). Except for RP11–73O6.3 and L3MBTL3 , there was no evidence of heterogeneity (I2<0.2) across the iCOGS, OncoArray, and GWAS datasets included in our analyses (Supplementary Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 34 associated genes are located at known breast cancer susceptibility loci (Tables 2–3). Among them, 23 have not yet been implicated as genes responsible for association signals identified at these loci through expression quantitative trait loci (eQTL) and/or functional studies, and do not harbor GWAS or fine-mapping identified risk variants (Table 2), while the other eleven ( KLHDC7A 7 , ALS2CR12 31 , CASP8 31,32 , ATG10 9 , SNX32 33 , STXBP4 34,35 , ZNF404 8 , ATP6AP1L 9 , RMND1 17, L3MBTL3 6 , and RCCD1 10 ) had been reported as potential causal genes at breast cancer susceptibility loci or harbor GWAS or fine-mapping identified risk variants (Table 3). Except for RP11–73O6.3 and L3MBTL3 , there was no evidence of heterogeneity (I2<0.2) across the iCOGS, OncoArray, and GWAS datasets included in our analyses (Supplementary Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, there are single reports presenting SNPs of the CASP-8 gene as prognostic factors in lung cancer patients. In fact, the available data (from breast tissue) indicate that it is the AA and not the GG genotype of the CASP-8 gene that is usually associated with lower (and therefore generally unfavorable, apoptosis-inhibiting) expression of the encoded protein [ 42 ]. However, it should be taken into account that this gene may be regulated differently in different tissues and different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A study in the United Kingdom and the United States has indicated that rs3769821 can increase the risk of breast cancer up to 17% (OR, 1.17; 95% CI, 1.05‐1.30; P = 0.0032) . As the functional analysis has pointed out the relationship between the risk allele and expression level in breast cancer, rs3769821 may be a potential diagnostic and prognostic factor for breast cancer . To confirm the results, large well‐designed cohort studies are essential.…”
Section: Discussionmentioning
confidence: 99%